[INVITED] Biosensing with nanoaperture optical tweezers. (January 2019) - Gordon, Reuven
Highlights: Nanoapertures in metal films allow for optical trapping of proteins, DNA fragments and other biomolecules, as well as small viruses. They provide a label free approach to identify proteins based on their trapping dynamics, including in unpurified solutions. Protein interactions with DNA and small molecules have been measured with this approach. The vibrational modes of the trapped nanoparticles can be measured using a modification of nanoaperture trapping called extraordinary acoustic Raman (EAR). Abstract: Nanoaperture optical tweezers extend the range of optical tweezers to dielectric particles below 50 nm in size. This allows for optical trapping of proteins, DNA fragments and other biomolecules, as well as small viruses. With this label-free, tether-free approach proteins have been trapped, sized and their conformational changes observed in real-time. The molecular weight of proteins in the nanoaperture trap was determined from their Brownian motion statistics. This is useful for analysis of heterogeneous solutions: since this is a single molecule technique, it can be operated in "dirty" solutions with minimal sample preparation. The acoustic modes of proteins, DNA fragments and other trapped nanoparticles can be measured using a nanoaperture optical tweezer with two lasers creating a GHz to THz beat frequency. Interactions between proteins and DNA, small molecules (i.e., binding) and other proteins have also been demonstrated. This single molecule technique allows for measuring the dissociation constants of small molecules binding to proteins, both at equilibrium and at the single molecule level. For DNA fragments in the trap, it has been shown that the protein p53 can suppress unzipping and mutant p53 is ineffective to do so. This is promising for the discovery of drugs that effectively restore the function to p53. Integration of nanoapertures on the ends of fibers allows for translocation of the trapped object and may function as an optical "nanopipette" for microwell single molecule protein sampling. There is also potential to combine nanoapertures with nanopore translocation studies as well as fluorescence correlation microscopy studies and several researchers are already pursuing these areas of research.